DISIPLIN KERJA DAN KEMAMPUAN KERJA DALAM MEMPENGARUHI KINERJA TENAGA KEPENDIDIKAN MELALUI VARIABEL MEDIASI KEPUASAN KERJA PADA YAYASAN MISBAHUL HIDAYAH SUBOH KABUPATEN SITUBONDO - Zulkarnain, Moch Irfan; Ediyanto, Ediyanto; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2023)
Human resources are people who can and want to help an organization achieve its goals. The aim of this research is to determine the increase in Work Discipline, Work Ability, Performance and Job Satisfaction of human resources at the Misbahul Hidayah Suboh Foundation, Situbondo Regency. The population in this study was employees of the Misbahul Hidayah Suboh Foundation, Situbondo Regency. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing for this research used Partial Least Square-Structural Equation Modeling (PLS- SEM). The results of testing the direct influence hypothesis using the Smart PLS 3.0 application show that Work Discipline has a significant positive effect on Job Satisfaction. Work Ability has a significant positive effect on Job Satisfaction. Work Discipline has a negative but not significant effect on Performance. Work Ability has a significant positive effect on Performance. Job Satisfaction has a significant positive effect. Work Discipline on Performance through Job Satisfaction has a positive but not significant effect. Work Ability on Performance through Job Satisfaction has a positive significant effect.